Supramolecular Thixotropic Ionogel Electrolyte for Sodium Batteries - Shipeng Chen; Li Feng; Xiaoji Wang; Yange Fan; Yubin Ke; Lin Hua; Zheng Li; Yimin Hou; Baoyu Xue (Gels, 2022)
Owing to the potential of sodium as an alternative to lithium as charge carrier, increasing attention has been focused on the development of high-performance electrolytes for Na batteries in recent years. In this regard, gel-type electrolytes, which combine the outstanding ionic conductivity of liquid electrolytes and the safety of solid electrolytes, demonstrate immense application prospects. However, most gel electrolytes not only need a number of specific techniques for molding, but also typically suffer from breakage, leading to a short service life and severe safety issues. In this study, a supramolecular thixotropic ionogel electrolyte is proposed to address these problems. This thixotropic electrolyte is formed by the supramolecular self-assembly of D-gluconic acetal-based gelator (B8) in an ionic liquid solution of a Na salt, which exhibits moldability, a high ionic conductivity, and a rapid self-healing property. The ionogel electrolyte is chemically stable to Na and exhibits a good Na+ transference number. In addition, the self-assembly mechanism of B8 and thixotropic mechanism of ionogel are investigated. The safe, low-cost and multifunctional ionogel electrolyte developed herein supports the development of future high-performance Na batteries.